2020
DOI: 10.3390/ijms21010305
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk with Jasmonic Acid Integrates Multiple Responses in Plant Development

Abstract: To date, extensive studies have identified many classes of hormones in plants and revealed the specific, nonredundant signaling pathways for each hormone. However, plant hormone functions largely overlap in many aspects of plant development and environmental responses, suggesting that studying the crosstalk among plant hormones is key to understanding hormonal responses in plants. The phytohormone jasmonic acid (JA) is deeply involved in the regulation of plant responses to biotic and abiotic stresses. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 106 publications
0
73
0
1
Order By: Relevance
“…JA antagonistically interacts with CKs to regulate xylem development. CKs negatively regulate xylem differentiation, while JA treatment promotes the formation of extra xylem [139].…”
Section: At4g39400mentioning
confidence: 99%
“…JA antagonistically interacts with CKs to regulate xylem development. CKs negatively regulate xylem differentiation, while JA treatment promotes the formation of extra xylem [139].…”
Section: At4g39400mentioning
confidence: 99%
“…It regulates the movement of the stomatal guard cells [102]. Jasmonates act as stress hormones that play an important role in the plant response to biotic and abiotic stresses [103]. In general, JA inhibits plant growth and modulate many growth and developmental processes of plants including root, shoot and leaf growth, trichome and tuber formation, fruit ripening and leaf senescence [104].…”
Section: Phytohormone Treatmentmentioning
confidence: 99%
“…To understand the mechanisms of these stress responses and enable approaches to improve stress tolerance, extensive studies have identified many genetic components that mediate plant responses to abiotic stresses. These studies further revealed that abscisic acid (ABA) and jasmonic acid (JA) are key signaling molecules that mediate plant responses to abiotic stresses [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%